Analysis of the Effectiveness of Soil Moisture Sensors to Increase Productivity in Smart Agriculture - Ramko Anggi Dwipayana; Aris Wahyudi Wohir (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
This study aims to analyze the effectiveness of soil moisture sensors in increasing productivity in smart agriculture systems. Along with the increasing demand for efficient and sustainable farming methods, soil moisture sensor technology is a promising solution for accurately monitoring and controlling soil moisture. This sensor helps optimise irrigation by providing real-time data that makes it easy to adjust the water supply according to plant needs, thereby reducing waste and saving water. This study was conducted on a test area of 1 hectare with two main treatments: land with an irrigation system based on soil moisture sensors and land with a conventional irrigation system. For three months, measurements of crop productivity and water use were carried out on both lands. The results show that the use of soil moisture sensors can increase plant productivity by 25% and save water use by up to 30% compared to traditional irrigation methods. These findings provide a solid foundation for the further development of resource-efficient and environmentally friendly smart farming systems. The results of this study are expected to encourage farmers to adopt soil moisture sensor technology to improve efficiency and sustainability in their agricultural practices.